A survey of factors influencing standards and outcomes of care for patients with diabetes mellitus attending the urban health centre and its community clinics in South India: a cross-sectional study - Pricilla, Ruby Angeline; Muhammad, Falah Pulikkadan; Vijayakumar, Priyadarshini; Mukherjee, Pavan; Sankarapandian, Venkatesan; Rahman, Sajitha M. F. (International Journal Of Community Medicine And Public Health, 2025)
Background: Diabetes mellitus is a rising health challenge in south-east Asia and India in particular. The World Health Organization advocates for effective management of diabetes at the primary and secondary care centres. The first contact and longitudinal care of patients with diabetes should be effective to improve their health outcomes. This study was undertaken to determine the standard and outcome of care and the factors influencing them among patients with diabetes attending the low-resourced urban health centre (UHC) and its community clinics (CCs) in south India. Methods: A cross-sectional study was done among adults with diabetes for more than a year. A structured questionnaire was used to collect data from 100 participants at the UHC and 200 from the CCs. Results: The mean standard of care score was significantly higher (p=0.00001) at the CCs than at the UHC. Overall, the glycemic control was poor. Participants who were male (p=0.03), belonging to religion other than Hindu (p=0.03), on oral drugs (p=0.004) and no complications (p=0.02) had better glycemic control at the UHC. At the CCs, those with ≤ six years of diabetes (p=0.001), with ≤ five clinic visits (p=0.004), on oral drugs (p=0.01) and without complications (p=0.04) had better glycemic control. Conclusions: Better glycemic control was noted among patients with lesser duration of diabetes, those without complications and those on oral hypoglycemics alone. The spectrum of challenges in improving standard of care in low resourced communities is beyond the implementation of clinical guidelines alone.